Advanced SPM studies on the growth of ultrathin films of organic semiconductors at metal and dielectric interfaces - Straub, Andreas <1980> (Alma Mater Studiorum - Università di Bologna, 2011)
Many studies on the morphology, molecular orientation, device performance, substrate nature and growth parameter dependence have been carried out since the proposal of Sexithiophene (6T) for organic electronics [ ] However, these studies were mostly performed on films thicker than 20nm and without specifically addressing the relationship between morphology and molecular orientation within the nano and micro structures of ultrathin films of 0-3 monolayers. In 2004, the observation that in OFETs only the first few monolayers at the interface in contact with the gate insulator contribute to the charge transport [ ], underlined the importance to study submonolayer films and their evolution up to a few monolayers of thickness with appropriate experimental techniques. We present here a detailed Non-contact Atomic Force Microscopy and Scanning Tunneling Microscopy study on various substrates aiming at the investigation of growth mechanisms. Most reported similar studies are performed on ideal metals in UHV. However it is important to investigate the details of organic film growth on less ideal and even technological surfaces and device testpatterns. The present work addresses the growth of ultra thin organic films in-situ and quasi real-time by NC-AFM. An organic effusion cell is installed to evaporate the organic material directly onto the SPM sample scanning stage.